2023
DOI: 10.3390/s23021001
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Classification Based on Population Nucleus Size Combining Microwave Impedance Spectroscopy and Machine Learning

Abstract: Many recent efforts in the diagnostic field address the accessibility of cancer diagnosis. Typical histological staining methods identify cancer cells visually by a larger nucleus with more condensed chromatin. Machine learning (ML) has been incorporated into image analysis for improving this process. Recently, impedance spectrometers have been shown to generate all-inclusive lab-on-a-chip platforms to detect nucleus abnormities. In this paper, a wideband electrical sensor and data analysis paradigm that can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The combined use of feature selection and classification together can provide insights when sensitivity makes the separation of populations difficult. An example of this is our previous work classifying cells in populations using electrical impedance data at 201 frequencies ranging from 9 kHz to 9 GHz to identify changes in nucleus size [58]. In this work, we found that the combination of feature selection using recursive feature elimination (RFE) when combined with SVM both improved the accuracy of predictions but also could identify the most relevant frequency features.…”
Section: Classification Of Cell Differencesmentioning
confidence: 87%
“…The combined use of feature selection and classification together can provide insights when sensitivity makes the separation of populations difficult. An example of this is our previous work classifying cells in populations using electrical impedance data at 201 frequencies ranging from 9 kHz to 9 GHz to identify changes in nucleus size [58]. In this work, we found that the combination of feature selection using recursive feature elimination (RFE) when combined with SVM both improved the accuracy of predictions but also could identify the most relevant frequency features.…”
Section: Classification Of Cell Differencesmentioning
confidence: 87%
“…The differences have been detected using a nanoneedle bioarray 209 . In our group, model muscle cell lines chemically treated to present elevated oxidative stress 227 or intracellular calcium levels 228 have also been shown to present distinct electrical signatures compared to untreated cells. Since elevated oxidative stress and alteration in calcium signalling are typical characteristics of ME/CFS skeletal muscle tissues, the electrical characteristics of muscle cells have been proposed as a signature to define ME/CFS muscle dysfunction, while this idea has yet to be tested using clinical samples.…”
Section: Perspectives: Where We Are Looking and Where We Might Lookmentioning
confidence: 99%
“…Recently, impedance spectrometers have been shown to generate all-inclusive lab-on-a-chip platforms to detect nucleus abnormalities. The paper, presented by Ferguson et al [ 117 ], is a proof-of-concept study on the classification of cancerous cells using a biosensor that employs impedance-based spectroscopy to identify the type of cells based on the size of their nucleus. The biosensor consists of a microfluidic channel attached to a quartz substrate containing an ultra-wideband waveguide.…”
Section: Lab-on-a-chip In Cancer Detectionmentioning
confidence: 99%